Pengaruh Pengungkapan Corporate Social Responsibility, Investment Opportunity Set dan Struktur Modal pada Nilai Perusahaan - Sabina Rini, Kadek Dina; Mimba, Ni Putu Sri Harta (E-Jurnal Akuntansi, 2019)
The samples used in this study were 28 companies so that there were 140 observations. The research sample was taken using purposive sampling technique. The analysis technique used in this study is multiple linear regression. The results of this study indicate that the disclosure variables of corporate social responsibility have a positive effect on firm value. The variable investment opportunity set has a positive effect on firm value. Capital structure variables have a positive effect on firm value. Theoretical implications of the research show that the results of the research are in line with signal theory. The practical implications of research can be taken into consideration for investors in making decisions by looking at information on CSR disclosures, IOS and company capital structure. Keywords : Corporate value, corporate social responsibility, investment opportunity set, capital structure.